1998
DOI: 10.1093/jnci/90.20.1563
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of p53 Autoantibodies in the Sera of Patients With Non-Small-Cell Lung Cancer

Abstract: In NSCLC, the incidence of p53 autoantibodies is associated with histologic type, stage, and p53 overexpression--but not with patient survival. Our data do not support the clinical utility of p53 autoantibodies as diagnostic or prognostic markers in patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…For example, antibodies to NY-ESO-1 are found in ≈50% of stage IV melanoma patients expressing NY-ESO-1 in their tumor, but the overall frequency in melanoma is about 8% when considering earlier stages (with less frequent NY-ESO-1 expression) and nonexpressing tumors (31). Similarly, p53 and XAGE-1 are immunogenic in 10-30% of non-small-cell lung cancers, depending on type and stage, but very rarely so in melanoma (35)(36)(37). Therefore, in the current study, the frequencies of seroreactivity observed against top antigens in pancreatic and ovarian cancer patients have to be placed in the context of cognate antigen expression frequency, tumor type selected, and stage.…”
Section: Discussionmentioning
confidence: 99%
“…For example, antibodies to NY-ESO-1 are found in ≈50% of stage IV melanoma patients expressing NY-ESO-1 in their tumor, but the overall frequency in melanoma is about 8% when considering earlier stages (with less frequent NY-ESO-1 expression) and nonexpressing tumors (31). Similarly, p53 and XAGE-1 are immunogenic in 10-30% of non-small-cell lung cancers, depending on type and stage, but very rarely so in melanoma (35)(36)(37). Therefore, in the current study, the frequencies of seroreactivity observed against top antigens in pancreatic and ovarian cancer patients have to be placed in the context of cognate antigen expression frequency, tumor type selected, and stage.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of p53-Ab, often reflecting p53 mutation, has been associated with poor prognosis and shorter survival in NSCLC (Quinlan et al, 1992;Marchetti et al, 1993;Harpole et al, 1995;Laudanski et al, 1998). Some groups have found no such correlation (McLaren et al, 1992;Mitsudomi et al, 1998) and others have shown a favourable prognosis (Lee et al, 1995;Bergqvist et al, 1998). P53 in SCLC has not been studied as extensively, but there are two large studies that we can compare our results with.…”
Section: Serum P53 Antibodies In Sclc 1421mentioning
confidence: 99%
“…Most recently p53 mutations detectable in tumour samples have been shown to be not only an independent marker for poor outcome in resectable stage I NSCLC (Harpole, 1995), but also to correlate with nodal involvement and thus shorter survival (Marchetti et al, 1993). In NSCLC there is a prevalence of p53 antibodies of around 24% correlated with a much higher rate of p53 mutation, of the order of 60-70% (Schlichtholz et al, 1992;Winter et al, 1992;Wild et al, 1995;Komiya et al, 1997;Rosenfeld et al, 1997;Bergqvist et al, 1998;Iizasa et al, 1998;Laudanski et al, 1998;Mitsudomi et al, 1998;Segawa et al, 1998). Studies have shown a decrease in levels of p53-Abs in patients treated for lung cancer (Zalcman et al, 1998).…”
mentioning
confidence: 99%
“…The presence of anti-p53 antibodies has been frequently found in the sera of patients with lung cancer containing p53 mutations (Iizasa et al, 1998). In a study with 188 patients with NSCLC, anti-p53 antibodies were detected in over 20% of the patients although it is more frequently detected in patients with more advanced disease (Mitsudomi et al, 1998). Several other auto-antibodies have recently been identi®ed as potential biomarkers in lung cancer detection.…”
Section: Detect Molecular Changes In Bloodmentioning
confidence: 99%